Degradation of Lignosulfonate to Vanillic Acid Using Ferrate. (25th December 2022) - Klein, Jana; Kupec, Robin; Stöckl, Markus; Waldvogel, Siegfried R.
Abstract: A new method is presented using electrochemically generated ferrate to degrade the technically relevant bio‐based side‐stream products, lignin and lignosulfonate. An exclusive degradation to vanillic acid is found, which was previously a reported by‐product. As a natural resource, lignin can be utilized to substitute fossil‐based chemicals in the industry to reduce greenhouse gas emissions and positively impact climate change. Ferrate is generated from grey cast iron sacrificial anodes in 40 wt% NaOH with a current efficiency of over 22% at a current density of up to 100 mA cm −2 . Vanillic acid is obtained as the sole product after optimizing the reaction parameters, temperature, time, and ferrate concentration for the lignosulfonate degradation via the design of experiments. As a result, yields of 7.2 wt% of the flavoring agent and antioxidant vanillic acid are achieved. The presented two‐step degradation provides an inexpensive path for the production of vanillic acid on a laboratory scale from a highly abundant bio‐based side‐stream. Abstract : Electrochemically generated ferrate oxidation provides selectively vanillic acid from technically relevant types of lignin. The formation of vanillic acid is achieved by the alkaline reaction conditions and is improved with the green oxidizer ferrate.